Using the CAUSE Model to Understand Public Communication about Water Risks: Perspectives from Texas Groundwater District Officials on Drought and Availability - VanDyke, Matthew S.; King, Andy J. (Risk Analysis, 2018)
Abstract Public communication about drought and water availability risks poses challenges to a potentially disinterested public. Water management professionals, though, have a responsibility to work with the public to engage in communication about water and environmental risks. Because limited research in water management examines organizational communication practices and perceptions, insights into research and practice can be gained through investigation of current applications of these risk communication efforts. Guided by the CAUSE model, which explains common goals in communicating risk information to the public (e.g., creating Confidence, generating Awareness, enhancing Understanding, gaining Satisfaction, and motivating Enactment), semistructured interviews of professionals ( N = 25) employed by Texas groundwater conservation districts were conducted. The interviews examined how CAUSE model considerations factor in to communication about drought and water availability risks. These data suggest that many work to build constituents’ confidence in their districts. Although audiences and constituents living in drought‐prone areas were reported as being engaged with water availability risks and solutions, many district officials noted constituents’ lack of perceived risk and engagement. Some managers also indicated that public understanding was a secondary concern of their primary responsibilities and that the public often seemed apathetic about technical details related to water conservation risks. Overall, results suggest complicated dynamics between officials and the public regarding information access and motivation. The article also outlines extensions of the CAUSE model and implications for improving public communication about drought and water availability risks.

The influence of impact-based severe weather warnings on risk perceptions and intended protective actions - Potter, Sally H.; Kreft, Peter V.; Milojev, Petar; Noble, Chris; Montz, Burrell; Dhellemmes, Amandine; Woods, Richard J.; Gauden-Ing, Sarah (International Journal of Disaster Risk Reduction, 2018)

Hydrological dynamics of prairie pothole wetlands: Dominant processes and landscape controls under contrasted conditions - Haque, Aminul; Ali, Genevieve; Badiou, Pascal (Hydrological Processes, 2018)
Abstract Numerous studies have examined the impact of prairie pothole wetlands on overall watershed dynamics. However, very few have looked at individual wetland dynamics across a continuum of alteration status using subdaily hydrometric data. Here, the importance of surface and subsurface water storage dynamics in the prairie pothole region was documented by (1) characterizing surface fill–spill dynamics in intact and consolidated wetlands; (2) quantifying water‐table fluctuations and the occurrence of overland flow downslope of fully drained wetlands; (3) assessing the relation (or lack thereof) between intact, consolidated or drained wetland hydrological behaviour, and stream dynamics; and (4) relating wetland hydrological behaviour to landscape characteristics. Focus was on southwestern Manitoba, Canada, where ten intact, three consolidated, seven fully drained wetlands, and a nearby creek were monitored over two years with differing antecedent storage conditions. Hourly hydrological time series were used to compute behavioural metrics reflective of year‐specific and season‐specific wetland dynamics. Behavioural metrics were then correlated to wetland physical characteristics to identify landscape controls on wetland hydrology. Predictably, more frequent spillage or overland flow was observed when antecedent storage was high. Consolidated wetlands had a high degree of water permanence and a greater frequency of fill–spill events than intact wetlands. Shallow and highly responsive water tables were present downslope of fully drained wetlands. Potential wetland–stream connectivity was also inferred via time‐series analysis, while some landscape characteristics (e.g., wetland surface, catchment area, and storage volume) strongly correlated with wetland behavioural metrics. The nonstationarity of dominant processes was, however, evident through the lack of consistent correlations across seasons. This, therefore, highlights the importance of combining multiyear high‐frequency hydrometric data and detailed landscape analyses in wetland hydrology studies.

Serious Games as Planning Support Systems: Learning from Playing Maritime Spatial Planning Challenge 2050 - Jean, Steven; Gilbert, Laura; Medema, Wietske; Keijser, Xander; Mayer, Igor; Inam, Azhar; Adamowski, Jan (Water, 2018)
The inherent complexity of planning at sea, called maritime spatial planning (MSP), requires a planning approach where science (data and evidence) and stakeholders (their engagement and involvement) are integrated throughout the planning process. An increasing number of innovative planning support systems (PSS) in terrestrial planning incorporate scientific models and data into multi-player digital game platforms with an element of role-play. However, maritime PSS are still early in their innovation curve, and the use and usefulness of existing tools still needs to be demonstrated. Therefore, the authors investigate the serious game, MSP Challenge 2050, for its potential use as an innovative maritime PSS and present the results of three case studies on participant learning in sessions of game events held in Newfoundland, Venice, and Copenhagen. This paper focusses on the added values of MSP Challenge 2050, specifically at the individual, group, and outcome levels, through the promotion of the knowledge co-creation cycle. During the three game events, data was collected through participant surveys. Additionally, participants of the Newfoundland event were audiovisually recorded to perform an interaction analysis. Results from survey answers and the interaction analysis provide evidence that MSP Challenge 2050 succeeds at the promotion of group and individual learning by translating complex information to players and creating a forum wherein participants can share their thoughts and perspectives all the while (co-) creating new types of knowledge. Overall, MSP Challenge and serious games in general represent promising tools that can be used to facilitate the MSP process.

Assessing the potential impacts of dam operation on daily flow at ungauged river reaches - Mailhot, A.; Talbot, G.; Ricard, S.; Turcotte, R.; Guinard, K. (Journal of Hydrology: Regional Studies, 2018)

Temporal and depth variation of water quality due to thermal stratification in Karkheh Reservoir, Iran - Noori, Roohollah; Berndtsson, Ronny; Franklin Adamowski, Jan; Rabiee Abyaneh, Maryam (Journal of Hydrology: Regional Studies, 2018)

Applying the Theory of Reliability to the Assessment of Hazard, Risk and Safety in a Hydrologic System: A Case Study in the Upper Sola River Catchment, Poland - Ozga-Zielinski, Bogdan; Adamowski, Jan; Ciupak, Maurycy (Water, 2018)

An Entropy-Based Approach to Fuzzy Multi-objective Optimization of Reservoir Water Quality Monitoring Networks Considering Uncertainties - Pourshahabi, Shokoufeh; Nikoo, Mohammad Reza; Raei, Ehsan; Adamowski, Jan Franklin (Water Resources Management, 2018)

Addressing the incorrect usage of wavelet-based hydrological and water resources forecasting models for real-world applications with best practices and a new forecasting framework - Quilty, John; Adamowski, Jan (Journal of Hydrology, 2018)

A New Approach to Predict Daily pH in Rivers Based on the “à trous” Redundant Wavelet Transform Algorithm - Rajaee, Taher; Ravansalar, Masoud; Adamowski, Jan F.; Deo, Ravinesh C. (Water, Air, & Soil Pollution, 2018)

Assessing structural, functional and effective hydrologic connectivity with brain neuroscience methods: State-of-the-art and research directions - Rinderer, Michael; Ali, Genevieve; Larsen, Laurel G. (Earth-Science Reviews, 2018)

Exploring the effects of climatic variables on monthly precipitation variation using a continuous wavelet-based multiscale entropy approach - Roushangar, Kiyoumars; Alizadeh, Farhad; Adamowski, Jan (Environmental Research, 2018)

Groundwater Pollution Sources Apportionment in the Ghaen Plain, Iran - Vesali Naseh, Mohammad; Noori, Roohollah; Berndtsson, Ronny; Adamowski, Jan; Sadatipour, Elaheh (International Journal of Environmental Research and Public Health, 2018)

Effect of Land Use Change on Soil Carbon Storage over the Last 40 Years in the Shi Yang River Basin, China - Yang, Shurong; Sheng, Danrui; Adamowski, Jan; Gong, Yifan; Zhang, Jian; Cao, Jianjun (Land, 2018)

Influences of afforestation policies on soil moisture content in China’s arid and semi-arid regions - Cao, Jianjun; Tian, Hong; Adamowski, Jan F.; Zhang, Xiaofang; Cao, Zijian (Land Use Policy, 2018)

Multi-household grazing management pattern maintains better soil fertility - Cao, Jianjun; Xu, Xueyun; Deo, Ravinesh C.; Holden, Nicholas M.; Adamowski, Jan F.; Gong, Yifan; Feng, Qi; Yang, Shurong; Li, Mengtian; Zhou, Junju; Zhang, Jian; Liu, Minxia (Agronomy for Sustainable Development, 2018)

Relationship between water quality and macro-scale parameters (land use, erosion, geology, and population density) in the Siminehrood River Basin - Bostanmaneshrad, Farshid; Partani, Sadegh; Noori, Roohollah; Nachtnebel, Hans-Peter; Berndtsson, Ronny; Adamowski, Jan Franklin (Science of The Total Environment, 2018)

Multi-step water quality forecasting using a boosting ensemble multi-wavelet extreme learning machine model - Barzegar, Rahim; Asghari Moghaddam, Asghar; Adamowski, Jan; Ozga-Zielinski, Bogdan (Stochastic Environmental Research and Risk Assessment, 2018)

Evidence for the occurrence of hydrogeochemical processes in the groundwater of Khoy plain, northwestern Iran, using ionic ratios and geochemical modeling - Barzegar, Rahim; Asghari Moghaddam, Asghar; Nazemi, Amir Hossein; Adamowski, Jan (Environmental Earth Sciences, 2018)

Bank erosion processes measured with UAV-SfM along complex banklines of a straight mid-sized river reach - Duró, Gonzalo; Crosato, Alessandra; Kleinhans, Maarten G.; Uijttewaal, Wim S. J. (Earth Surface Dynamics, 2018)
We apply structure from motion (SfM) photogrammetry with imagery from an unmanned aerial vehicle (UAV) to measure bank erosion processes along a mid-sized river reach. This technique offers a unique set of characteristics compared to previously used methods to monitor banks, such as high resolution and relatively fast deployment in the field. We analyse the retreat of a 1.2 km restored bank of the Meuse River which has complex vertical scarps laying on a straight reach, features that present specific challenges to the UAV-SfM application. We surveyed eight times within a year with a simple approach, combining different photograph perspectives and overlaps to identify an effective UAV flight. The accuracy of the digital surface models (DSMs) was evaluated with real-time kinematic (RTK) GPS points and airborne laser scanning of the whole reach. An oblique perspective with eight photo overlaps and 20 m of cross-sectional ground-control point distribution was sufficient to achieve the relative precision to observation distance of ∼1 : 1400 and 3 cm root mean square error (RMSE), complying with the required accuracy. A complementary nadiral view increased coverage behind bank toe vegetation. Sequential DSMs captured signatures of the erosion cycle such as mass failures, slump-block deposition, and bank undermining. Although UAV-SfM requires low water levels and banks without dense vegetation as many other techniques, it is a fast-in-the-field alternative to survey reach-scale riverbanks in sufficient resolution and accuracy to quantify bank retreat and identify morphological features of the bank failure and erosion processes. Improvements to the adopted approach are recommended to achieve higher accuracies.
Publisher: Copernicus GmbH
Keywords: Ouvrage_Collectif_Numéro1

Involving children in disaster risk reduction: the importance of participation - Pfefferbaum, Betty; Pfefferbaum, Rose L.; Van Horn, Richard L. (European Journal of Psychotraumatology, 2018)
Keywords: Ouvrage_Collectif_Numéro1

Ten Years of Science Based on the Canadian Precipitation Analysis: A CaPA System Overview and Literature Review - Fortin, V.; Roy, G.; Stadnyk, T.; Koenig, K.; Gasset, N.; Mahidjiba, A. (Atmosphere-Ocean, 2018)
Keywords: Ouvrage_Collectif_Numéro1

Rising sea levels and sinking property values: Hurricane Sandy and New York’s housing market - Ortega, Francesc; Taṣpınar, Süleyman (Journal of Urban Economics, 2018)
Keywords: Ouvrage_Collectif_Numéro1

When disaster strikes: Under-insurance in Australian households - Booth, Kate; Tranter, Bruce (Urban Studies, 2018)
In undertaking what we believe is the first national-scale study of its kind, we provide methodologically transparent, statistically robust insights into associations and potential unfolding effects of house and contents under-insurance. We identify new dimensions in the complex relationship between householders and insurance, including the salience of interpersonal – and likely institutional – trust. Under-insurance is (re)produced along socio-economic and geographical lines, with those of lower socio-economic status or living in cities more likely to be under-insured. Should a disaster strike, such communities are likely to suffer further disadvantage, especially if governments continue to shift the responsibility for risk onto households. Our findings support the observation that insurance can contribute to increasing socio-economic urban polarisation in light of natural disasters. We conclude by considering how under-insurance may contribute to growing urban social stratification, as well as how it may produce situated ethical and political responses that exceed neoliberal aspirations.
Keywords: Ouvrage_Collectif_Numéro1

Stochastic Richelieu River Flood Modeling - Safari, Maryam (École Polytechnique de Montréal, 2018)
RÉSUMÉ: La modélisation hydrodynamique est un élément fondamental du génie hydraulique. Elle permet de créer des modèles de bassins versants et de rivières pour la prédiction des inondations. La simulation des phénomènes d'inondation est un sujet de plus en plus important dans le domaine de la recherche en hydraulique. Compte tenu des exigences d'évaluation spécifiques dans les plans d'ingénierie des risques d'inondation, la modélisation des inondations devient très importante dans le génie hydraulique. La délimitation probabiliste des zones inondables joue un rôle déterminant dans les plans d'ingénierie des risques. Cette tâche importante est réalisable à l'aide de la simulation post-inondation et de la détermination des limites de l'étendue des inondations avec leurs probabilités d'occurrence correspondantes dans les zones étudiées. ABSTRACT: Hydrodynamic modeling including watershed, river and flood modeling is a fundamental part of hydraulic engineering. In this regard, simulation of flood phenomena is an increasingly important subject in hydraulic research domain. Considering specific evaluation requirements in flood risk engineering plans, flood modeling is becoming highly important based on hydrological method (rainfall-runoff) or hydraulic parameters in Hydraulic engineering.

A comparative assessment of hydrologic models of varying complexity applied to a semi-arid region (Sardinia, Italy). for climate change studies - Perra, Enrica (Università degli Studi di Cagliari - Université du Québec, Institut national de la recherche scientifique, 2018)
L'évaluation de l'impact hydrologique du changement climatique présente une importance particulière pour les bassins de la Méditerranée, qui sont très sensibles aux événements hydrologiques extrêmes. La modélisation des systèmes aussi complexes pour la gestion des ressources hydriques est un défi difficile. L'objectif global de ce travail est de contribuer au développement d'une approche de modélisation qui permette l'évaluation de l'impact hydrologique du changement climatique sur deux bassins de la Méditerranée, localisés en Sardaigne. Cette contribution se concentre sur deux sujets principaux: comprendre comment la représentation physique des modèles hydrologiques grave sur l'évaluation de l'impact hydrologique dû au changement climatique sur un bassin avec un climat semi-aride, le Rio Mannu di San Sperate, et montrer comme le modélisation avancé puisse aider à définir de mesures de modération et adaptation dans un système complexe enclin aux événements hydrique extrêmes, le Flumendosa, en conditions de changement climatique. Pour atteindre cet objectif le travail s'articule en trois phases. Les effets du changement climatique sur le bassin du Rio Mannu sont évalués à travers la comparaison des résultats de cinq modèles hydrologiques, CATchment HYdrology (CATHY), Soil and Water Assessment Tool (SWAT), TIN-based Real time Integrated Basin Simulator (tRIBS), TOPographic Kinematic APproximation and Integration-eXtended (TOPKAPI-X), and Water flow and balance Simulation Model (WASIM), en utilisant comme forçage atmosphérique les données de quatre combinaisons de modèles climatiques globaux (GCM) et régionaux (RCM). Pour évaluer les incertitudes une métrique récemment proposée est utilisée: les résultats des modèles sont comparés pendant une période de référence et future, en utilisant l'index de corrélation de Pearson et le bias de Duveiller. Même si certaines différences existent, en tout les modèles hydrologiques montrent une bonne concordance, et ils répondent de manière semblable à la réduction de la précipitation et à l'accroissement de la température prévu par les modèles climatiques. Il s'attend donc que le bassin dans l'avenir sera sujet à une réduction de la disponibilité de ressource hydrique, avec des conséquences négatives en particulier pour le secteur agricole. Une comparaison détaillée des réponses obtenue sur le même bassin avec trois modèles hydrologique à base physique avec différent degré pour ce qui concerne la représentation des procès physiques et des caractéristiques du terrain, CATHY, TOPKAPI-X, tRIBS, est effectué dans le but de tester la transférabilité des paramètres entre les trois modèles hydrologiques, avec une attention particulière sur les difficultés relevées dans les périodes de calibrage et validation. Tandis que les trois modèles ont répondu de manière semblable pendant la période de calibrage, significatives différences ont été relevées pendant la période de validation, caractérisé par un climat très sec, avec le modèle CATHY, qu'il a produit un très bas décharge. En conséquence, pour obtenir résultats satisfaisants avec le modèle CATHY, l’hypothèse de croûtage de sol a été assumée, sur la base dont la couche premier de sol a été modelée avec une conductibilité hydraulique saturée réduite. Finalement le modèle TOPKAPI-X est implémenté sur un des principaux bassins de la Sardaigne, d'importance stratégique pour le système hydrique de la région, le Flumendosa, afin d’évaluer les effets du changement climatique à plus grande échelle. Le modèle répond avec une diminution des valeurs de décharge, contenu hydrique et évapotranspiration réelle à la réduction de la précipitation et accroissement des températures prévus par les modèles climatiques en donnant aussi support à une scène future de carence de la ressource hydrique dans ce bassin de la zone Méditerranéenne. Assessing the hydrologic impacts of climate change is of great importance in the Mediterranean basins, which are heavily sensitive to climate variability, with significant impacts on water resources and hydrologic extremes. Modeling such complex systems to manage water resources and predict hydrologic extremes is a difficult task. The overall aim of the work described in this thesis is to bring a contribution in developing a modeling approach that allows evaluation of local hydrologic impacts of climate changes in two Mediterranean catchments located in Sardinia. This contribution revolves around two main themes: understanding how physical representation of hydrologic models can affect hydrologic impact assessment under climate change on a semi-arid basin of the Mediterranean region, the Rio Mannu catchment, and demonstrating how advanced hydrologic modeling can help in defining adaptation measures in a complex water system, the Flumendosa basin, under climate change. The work to achieve the general objective is elaborated into three stages. The effects of climate change are evaluated on the Rio Mannu catchment through comparison of the results from five hydrologic models, CATchment HYdrology (CATHY), Soil and Water Assessment Tool (SWAT), TIN-based Real time Integrated Basin Simulator (tRIBS), TOPographic Kinematic APproximation and Integration-eXtended (TOPKAPI-X), and Water flow and balance Simulation Model (WASIM), and using as atmospheric input outputs of four climate global (GCM) and regional (RCM) model combinations. In order to evaluate uncertainties, a recently proposed metric is used: climate and hydrologic models results are compared in terms of agreement with each other in reference and future periods using Pearson correlation values and Duveiller bias. Notwithstanding some differences, overall the five hydrologic models show good agreement, and they respond similarly to the reduced precipitation and increased temperatures predicted by the climate models, lending strong support to a future scenario of increased water shortages for this region of the Mediterranean, with negative consequences especially for the agricultural sector. Detailed comparison of the responses obtained with three physically based hydrologic models, but to varying degrees as regards physical processes and terrain features representation – CATHY, tRIBS, and TOPKAPI-X – on the same catchment is carried out, with the aim to test the transferability of parameters between the three hydrologic models, focusing in particular on the calibration and validation difficulties. While the three hydrologic models responded similarly during the calibration year, significant differences were found for the drier validation period for the CATHY model, which produced very low streamflow. To obtain satisfactory results for the CATHY model, an hypothesis of soil crusting was assumed and the first soil layer was modeled with a lower saturated hydraulic conductivity. Finally, the TOPKAPI-X model is applied on a large Sardinian basin prone to extreme flood events, the Flumendosa basin, to assess the hydrologic impact of climate change at much larger scale. The model responds with decreasing value of discharge, soil water content, and actual evapotranspiration to the reduced precipitation and increased temperature predicted by the climate models, lending strong support to a future scenario of increased water shortages also in this basin of the Mediterranean region. La valutazione dell’impatto idrologico del cambiamento climatico riveste particolare importanza per i bacini del Mediterraneo, sensibili ad eventi idrologici estremi. Modellizzare dei sistemi così complessi per la gestione della risorse idriche è una sfida difficile. L’obiettivo globale di questo lavoro è contribuire allo sviluppo di un approccio modellistico che consenta la valutazione dell’impatto idrologico del cambiamento climatico su due bacini del Mediterraneo localizzati in Sardegna. Questo contributo si focalizza su due temi principali: capire come la rappresentazione fisica dei modelli idrologici incida sulla valutazione dell’impatto idrologico dovuto al cambiamento climatico su un bacino con un clima semi-arido, il Rio Mannu di San Sperate, e dimostrare come la modellizzazione avanzata possa aiutare nel definire misure di adattamento in un sistema idrico complesso incline ad eventi estremi, il Flumendosa, in condizioni di cambiamento climatico. Per raggiungere tale obiettivo il lavoro si articola in tre fasi. Gli effetti del cambiamento climatico sul bacino del Rio Mannu sono stati valutati attraverso il confronto dei risultati di cinque modelli idrologici, CATchment HYdrology (CATHY), Soil and Water Assessment Tool (SWAT), TIN-based Real time Integrated Basin Simulator (tRIBS), TOPographic Kinematic APproximation and Integration-eXtended (TOPKAPI-X), and Water flow and balance Simulation Model (WASIM), utilizzando come forzante atmosferica gli output di quattro combinazioni di modelli climatici globali (GCM) e regionali (RCM). Per valutare le incertezze è stata utilizzata una metrica recentemente proposta: i risultati dei modelli sono stati comparati durante un periodo di riferimento e futuro, utilizzando l’indice di correlazione di Pearson e il bias di Duveiller. Pur con qualche differenza, complessivamente i modelli idrologici mostrano una buona concordanza tra loro, e rispondono in maniera simile alla riduzione della precipitazione e all’incremento della temperatura previsti dai modelli climatici. Ci si aspetta pertanto che il bacino nel futuro sarà soggetto ad una riduzione della disponibilità di risorsa idrica, con conseguenze negative in particolare per il settore agricolo. È stato effettuato un confronto dettagliato delle risposte ottenute sullo stesso bacino con tre modelli idrologici fisicamente basati di diverso grado per quanto riguarda la rappresentazione dei processi fisici e delle caratteristiche del terreno, CATHY, TOPKAPI-X, tRIBS, con lo scopo di testare la trasferibilità dei parametri tra i tre modelli idrologici, concentrandosi sulle difficoltà riscontrate nei periodi di calibrazione e validazione. Mentre i tre modelli hanno risposto in maniera simile durante il periodo di calibrazione, sono state riscontrate significative differenze durante il periodo di validazione, caratterizzato da un clima molto secco, con il modello CATHY, che ha prodotto una portata molto bassa. Pertanto, per ottenere risultati soddisfacenti con il modello CATHY, è stata assunta l’ipotesi di soil crusting, sulla base della quale il primo strato di suolo è stato modellato con una ridotta conducibilità idraulica satura. Infine il modello TOPKAPI-X è stato implementato su uno dei principali bacini sardi di importanza strategica per il sistema idrico della regione, il Flumendosa, per valutare gli effetti del cambiamento climatico a scala maggiore. Il modello risponde con una diminuzione dei valori di portata, contenuto idrico ed evapotraspirazione reale alla riduzione della precipitazione ed incremento della temperature previsto dai modelli climatici, dando supporto ad uno scenario futuro di carenza della risorsa idrica anche in questo bacino dell’area Mediterranea.

Effects of regional climate model spatial resolution on hydrological modelling of summer-fall floods in southern Quebec - Castaneda-Gonzalez, Mariana (École de technologie supérieure, 2018)
This study aims to evaluate the effects of the Canadian Regional Climate Model’s (CRCM) spatial resolution on summer-fall floods simulation. Seven different climate simulations issued from the fourth and the fifth version of the CRCM are employed. Four different climate simulations issued from the fourth version of the CRCM (CRCM4) are compared. They are composed of two simulations driven by the Canadian General Circulation Model (CGCM) and two driven by the ERA-40c reanalysis using grid meshes of 15 km and 45 km resolutions for each driver. Three climate simulations issued from the fifth version of the CRCM (CRCM5) driven by the ERA-Interim at 0.44° (≈ 48 km), 0.22° (≈ 24 km) and 0.11° (≈ 12 km) spatial resolutions are used. All comparisons are evaluated on a daily time-step for the 1961-1990 period (for CRCM4) and for the 1981-2010 period (for CRCM5). These seven simulations (four from CRCM4 and three from CRCM5) are used as input for two hydrological models of varying complexity (HSAMI and MOHYSE). Each model is calibrated using three different objective functions based on the Kling-Gupta Efficiency criteria (KGE) to target the summer-fall floods. Three seasonal indices are used to evaluate the CRCM outputs: bias (temperature), relative bias (precipitation) and variances ratio (temperature and precipitation). In an attempt to evaluate the effects of the spatial resolution on the hydrological modelling of summer-fall floods, streamflow simulations are generated using the seven climate datasets. The generated climate-driven streamflow simulations are analysed by two performance statistics: the seasonal values of KGE and the seasonal relative biases. Summer-fall floods are evaluated through the use of four flood indicators, the 2-year, 5-year, 10-year and 20-year return periods. The results revealed an impact of spatial resolution on climate model outputs (temperature and precipitation) and on summer-fall floods simulation by the two hydrological models and the three different calibration approaches, although this can be due to other elements such as domain size and climate model driver. The flood indicators demonstrate an increase on the summer-fall floods return periods with increasing resolution from both hydrological models. On the other hand the hydrological models structure and the calibration approaches did not show significant impacts on the summer-fall floods. The results highlight the need for further research to assess the additional uncertainty due to the impacts of the climate simulations spatial resolution on hydrological studies.

Establishing the Transitory Existence of Amorphous Phases in Crystallization Pathways by the CLASSIC NMR Technique - Hughes, Colan E.; Williams, P. Andrew; Kariuki, Benson M.; Harris, Kenneth D. M. (Chemphyschem: A European Journal of Chemical Physics and Physical Chemistry, 2018)
With the growing realization that crystallization processes may evolve through a sequence of different solid forms, including amorphous precursor phases, the development of suitable in-situ experimental probes is essential for comprehensively mapping the time-evolution of such processes. Here we demonstrate that the CLASSIC NMR (Combined Liquid- And Solid-State In-situ Crystallization NMR) strategy is a powerful technique for revealing the transitory existence of amorphous phases during crystallization processes, applying this technique to study crystallization of dl-menthol and l-menthol from their molten liquid phases. The CLASSIC NMR results provide direct insights into the conditions (including the specific time period) under which the molten liquid phase, transitory amorphous phases and final crystalline phases exist during these crystallization processes.

Evaluating Glacier Volume Changes since the Little Ice Age Maximum and Consequences for Stream Flow by Integrating Models of Glacier Flow and Hydrology in the Cordillera Blanca, Peruvian Andes - Huh, Kyung In; Baraër, Michel; Mark, Bryan G.; Ahn, Yushin (Water, 2018)
Evaluating the historical contribution of the volume loss of ice to stream flow based on reconstructed volume changes through the Little Ice Age (LIA) can be directly related to the understanding of glacier-hydrology in the current epoch of rapid glacier loss that has disquieting implications for a water resource in the Cordillera Blanca in the Peruvian Andes. However, the accurate prediction of the future glacial meltwater availability for the developing regional Andean society needs more extensive quantitative estimation from long-term glacial meltwater of reconstructed glacial volume. Modeling the LIA paleoglaciers through the mid-19th century (with the most extensive recent period of mountain glacier expansion having occurred around 1850 AD) in different catchments of the Cordillera Blanca allows us to reconstruct glacier volume and its change from likely combinations of climatic control variables and time. We computed the rate and magnitude of centennial-scale glacier volume changes for glacier surfaces between the LIA and the modern era, as defined by 2011 Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) Global Digital Elevation Model Version 2 (GDEM V2) and 2008 Light Detection and Range (LiDAR) data. The model simulation showed good agreement with the observed geomorphic data and the volume and surface area (V-S) scaling remained within the 25% error range in the reconstructed simulation. Also, we employed a recently demonstrated approach (Baraër, M. et al.) to calculate meltwater contribution to glacierized catchment runoff. The results revealed multiple peaks of both mean annual and dry season discharge that have never been shown in previous research on the same mountain range.
Keywords: Baraer_Michel

A review of the current state of knowledge of proglacial hydrogeology in the Cordillera Blanca, Peru - Glas, Robin; Lautz, Laura; McKenzie, Jeffrey; Mark, Bryan; Baraer, Michel; Chavez, Daniel; Maharaj, Laura (WIREs Water, 2018)
The rapidly melting glaciers of Peru are posing new risks to regional dry season water supplies, and this is evident in the Cordillera Blanca, the mountain range with the world's largest concentration of tropical glaciers. Permanent ice loss is causing reductions to dry season streamflow, which is coupled with shifting demands and control over water access and entitlements in the region. A full evaluation of hydrologic inputs is required to inform future water management in the relative absence of glaciers. Over the last decade, new studies have shown groundwater to be a significant component of the regional water budget during the dry season, and it cannot be ignored when accounting for water quality and quantity downstream of the Cordillera Blanca's alpine catchments. Distinctive common features of the Cordillera Blanca's proglacial catchments are sediment‐filled valleys that were once under proglacial lake conditions. The combination of lake sediments with other alpine depositional features results in storage and interseasonal release of groundwater that comprises up to 80% of the valley's streamflow during the driest months of the year. We summarize the emerging understanding of hydrogeologic processes in proglacial headwater systems of the region's principal river, the Rio Santa, and make suggestions for future research that will more clearly characterize the spatial distribution of stored groundwater within the mountain range. As glaciers continue to recede, differences in aquifer thickness and groundwater residence time between alpine catchments in the region will increasingly control dry season water availability at the local and basin scale. This article is categorized under: Science of Water > Hydrological Processes Science of Water > Water and Environmental Change Engineering Water > Planning Water
Keywords: Baraer_Michel

Targeting high robustness in snowpack modeling for Nordic hydrological applications in limited data conditions - Mas, Alexandre; Baraer, Michel; Arsenault, Richard; Poulin, Annie; Préfontaine, Jonathan (Journal of Hydrology, 2018)
Keywords: Baraer_Michel

Seasonal variations of steroid hormones released by wastewater treatment plants to river water and sediments: Distribution between particulate and dissolved phases - Yarahmadi, Hadis; Duy, Sung Vo; Hachad, Mounia; Dorner, Sarah; Sauvé, Sébastien; Prévost, Michèle (Science of The Total Environment, 2018)
Keywords: Dorner_Sarah

Bark type reflects growth potential of yellow birch and sugar maple at the northern limit of their range - Gauthier, Martin-Michel; Guillemette, François (Plant Ecology, 2018)
Keywords: Guillemette_Francois

Historical black carbon deposition in the Canadian High Arctic: a 250-year long ice-core record from Devon Island - Zdanowicz, Christian M.; Proemse, Bernadette C.; Edwards, Ross; Feiteng, Wang; Hogan, Chad M.; Kinnard, Christophe; Fisher, David (Atmospheric Chemistry and Physics, 2018)
Abstract. Black carbon aerosol (BC), which is emitted from natural and anthropogenic sources (e.g., wildfires, coal burning), can contribute to magnify climate warming at high latitudes by darkening snow- and ice-covered surfaces, and subsequently lowering their albedo. Therefore, modeling the atmospheric transport and deposition of BC to the Arctic is important, and historical archives of BC accumulation in polar ice can help to validate such modeling efforts. Here we present a > 250-year ice-core record of refractory BC (rBC) deposition on Devon ice cap, Canada, spanning the years from 1735 to 1992. This is the first such record ever developed from the Canadian Arctic. The estimated mean deposition flux of rBC on Devon ice cap for 1963–1990 is 0.2 mg m−2 a−1, which is at the low end of estimates from Greenland ice cores obtained using the same analytical method ( ∼ 0.1–4 mg m−2 a−1). The Devon ice cap rBC record also differs from the Greenland records in that it shows only a modest increase in rBC deposition during the 20th century. In the Greenland records a pronounced rise in rBC is observed from the 1880s to the 1910s, which is largely attributed to midlatitude coal burning emissions. The deposition of contaminants such as sulfate and lead increased on Devon ice cap in the 20th century but no concomitant rise in rBC is recorded in the ice. Part of the difference with Greenland could be due to local factors such as melt–freeze cycles on Devon ice cap that may limit the detection sensitivity of rBC analyses in melt-impacted core samples, and wind scouring of winter snow at the coring site. Air back-trajectory analyses also suggest that Devon ice cap receives BC from more distant North American and Eurasian sources than Greenland, and aerosol mixing and removal during long-range transport over the Arctic Ocean likely masks some of the specific BC source–receptor relationships. Findings from this study suggest that there could be a large variability in BC aerosol deposition across the Arctic region arising from different transport patterns. This variability needs to be accounted for when estimating the large-scale albedo lowering effect of BC deposition on Arctic snow/ice.
Keywords: Kinnard_Christophe

Revealing recent calving activity of a tidewater glacier with terrestrial LiDAR reflection intensity - Podgórski, Julian; Pętlicki, Michał; Kinnard, Christophe (Cold Regions Science and Technology, 2018)
Keywords: Kinnard_Christophe

Performance of temperature and radiation index models for point-scale snow water equivalent (SWE) simulations in the Moroccan High Atlas Mountains - Bouamri, H.; Boudhar, A.; Gascoin, S.; Kinnard, C. (Hydrological Sciences Journal, 2018)
Keywords: Kinnard_Christophe

Conflicts between recovery objectives: The case of housing reconstruction after the 2003 earthquake in Bam, Iran - Fayazi, Mahmood; Lizarralde, Gonzalo (International Journal of Disaster Risk Reduction, 2018)
Keywords: Lizarralde_Gonzalo

The Anthropocene and the Challenge of Implicated Time - Nobert, Sébastien (Science as Culture, 2018)
Keywords: Nobert_Sebastien

Meshfree particle numerical modelling of sub-aerial and submerged landslides - Tajnesaie, M.; Shakibaeinia, A.; Hosseini, K. (Computers & Fluids, 2018)
Keywords: Ahmad_Shakibaeinia

A multiphase meshfree particle method for continuum-based modeling of dry and submerged granular flows - Jafari Nodoushan, E.; Shakibaeinia, A.; Hosseini, K. (Powder Technology, 2018)
Keywords: Ahmad_Shakibaeinia

A Systematic Review of Physical Activity Interventions in Individuals with Binge Eating Disorders - Blanchet, Claudine; Mathieu, Marie-Ève; St-Laurent, Audrey; Fecteau, Shirley; St-Amour, Nathalie; Drapeau, Vicky (Current Obesity Reports, 2018)
Keywords: StAmour_Nathalie

Examining the challenges of simulating surface water–groundwater interactions in a post-glacial environment - Turgeon, Félix; Larocque, Marie; Meyzonnat, Guillaume; Dorner, Sarah; Bourgault, Marc-André (Canadian Water Resources Journal / Revue canadienne des ressources hydriques, 2018)
Keywords: Dorner_Sarah

Lower Respiratory Symptoms Associated With Environmental and Reconstruction Exposures After Hurricane Sandy - Gargano, Lisa M.; Locke, Sean; Jordan, Hannah T.; Brackbill, Robert M. (Disaster Medicine and Public Health Preparedness, 2018)
Abstract Objective In a population with prior exposure to the World Trade Center (WTC) disaster, this study sought to determine the relationship between Hurricane Sandy-related inhalation exposures and post-Sandy lower respiratory symptoms (LRS). Methods Participants included 3835 WTC Health Registry enrollees who completed Wave 3 (2011-2012) and Hurricane Sandy (2013) surveys. The Sandy-related inhalational exposures examined were: (1) reconstruction exposure; (2) mold or damp environment exposure; and (3) other respiratory irritants exposure. LRS were defined as wheezing, persistent cough, or shortness of breath reported on ≥1 of the 30 days preceding survey completion. Associations between LRS and Sandy exposures, controlling for socio-demographic factors, post-traumatic stress disorder, and previously reported LRS and asthma were examined using multiple logistic regression. Results Over one-third of participants (34.4%) reported post-Sandy LRS. Each of the individual exposures was also independently associated with post-Sandy LRS, each having approximately twice the odds of having post-Sandy LRS. We found a dose-response relationship between the number of types of Sandy-related exposures reported and post-Sandy LRS. Conclusions This study provides evidence that post-hurricane clean-up and reconstruction exposures can increase the risk for LRS. Public health interventions should emphasize the importance of safe remediation practices and recommend use of personal protective equipment. ( Disaster Med Public Health Preparedness . 2018;12:697-702)
Keywords: Ouvrage_Collectif_Numéro1

Bloated bodies and broken bricks: Power, ecology, and inequality in the political economy of natural disaster recovery - Sovacool, Benjamin K.; Tan-Mullins, May; Abrahamse, Wokje (World Development, 2018)

Input selection and data-driven model performance optimization to predict the Standardized Precipitation and Evaporation Index in a drought-prone region - Mouatadid, Soukayna; Raj, Nawin; Deo, Ravinesh C.; Adamowski, Jan F. (Atmospheric Research, 2018)

Challenges to enabling and implementing Natural Flood Management in Scotland - Waylen, K. A.; Holstead, K. L.; Colley, K.; Hopkins, J. (Journal of Flood Risk Management, 2018)
We explore factors that constrain implementation of Natural Flood Management ( NFM ), based on qualitative analysis of interviews with those influencing and enabling flood risk management in Scotland. NFM entails collaboration by multiple individuals and organisations to plan and deliver measures such as re‐meandering or buffer strips. Our interviewees identified many interacting issues. They particularly focused on difficulties in securing resources, and evidence gaps and uncertainties associated with NFM . Co‐ordination was not simple, often requiring new types of skill, expertise, and resources. NFM is thus outside the ‘comfort zone’ of many leading or engaged with flood risk management. These experiences echo and elaborate on other studies of attempts to encourage sustainable flood management. To tackle these challenges, practitioners should reflect how pre‐existing ideas and practices may shape and constrain new approaches to managing floods, while research is needed on specific strategies that can assist in enabling change.
Keywords: Ouvrage_Collectif_Numéro1

Disaster risk, climate change, and poverty: assessing the global exposure of poor people to floods and droughts - Winsemius, Hessel C.; Jongman, Brenden; Veldkamp, Ted I.E.; Hallegatte, Stephane; Bangalore, Mook; Ward, Philip J. (Environment and Development Economics, 2018)
Abstract People living in poverty are particularly vulnerable to shocks, including those caused by natural disasters such as floods and droughts. This paper analyses household survey data and hydrological riverine flood and drought data for 52 countries to find out whether poor people are disproportionally exposed to floods and droughts, and how this exposure may change in a future climate. We find that poor people are often disproportionally exposed to droughts and floods, particularly in urban areas. This pattern does not change significantly under future climate scenarios, although the absolute number of people potentially exposed to floods or droughts can increase or decrease significantly, depending on the scenario and region. In particular, many countries in Africa show a disproportionally high exposure of poor people to floods and droughts. For these hotspots, implementing risk-sensitive land-use and development policies that protect poor people should be a priority.

The Monetary Measurement of Flood Damage and the Valuation of the Proactive Policies in Sicily - Trovato, Maria Rosa; Giuffrida, Salvatore (Geosciences, 2018)
Although floods, as well as other natural disasters, can be considered as relevant causes of intra-generational inequalities, frequent catastrophes and the resulting damage to the territory can be seen as a consequence of a generalized indifference about future. Land protection is one of the societal issues typically concerning inter-generational solidarity, involving the administrative system in the implementation of proactive policies. In the last three decades, the widespread demand for subsidiarity has made local communities more and more independent, so that attention to the long-term effects—typically concerning the territorial system as a whole at geographical scale—has been dispersed, and the proactive policies that come from the central government have become more ineffective. Regarding the case of the 2009 flood in the Fiumedinisi-Capo Peloro river basin in North Eastern Sicily, we propose an economic valuation of the land protection policy. This valuation, compared to the cost of recovery of the damaged areas, can provide helpful information on the decision-making process concerning the trade-off between reactive and proactive land policy. The economic value of land protection was calculated by means of the method of the imputed preferences, to obtain a real measure of the social territorial value from the point of view of the harmony between social system and environment. This method consists of an estimate based on the attribution of the expenditures according to the importance of the different areas. Since the value of land protection has been calculated by discounting the expenditures stream, some considerations about the economic significance of the proactive policy are referred to the role played by the social discount rate in the inter-temporal economic calculation.

How Flood Experience and Risk Perception Influences Protective Actions and Behaviours among Canadian Homeowners - Thistlethwaite, Jason; Henstra, Daniel; Brown, Craig; Scott, Daniel (Environmental Management, 2018)
Keywords: Ouvrage_Collectif_Numéro1

The impact of flooding on aquatic ecosystem services - Talbot, Ceara J.; Bennett, Elena M.; Cassell, Kelsie; Hanes, Daniel M.; Minor, Elizabeth C.; Paerl, Hans; Raymond, Peter A.; Vargas, Rodrigo; Vidon, Philippe G.; Wollheim, Wilfred; Xenopoulos, Marguerite A. (Biogeochemistry, 2018)

Balancing upstream–downstream interests in flood risk management: experiences from a catchment‐based approach in Austria - Seher, W.; Löschner, L. (Journal of Flood Risk Management, 2018)
River floods usually do not stop at administrative borders. The respective location of municipalities along a river creates different options and dependencies, commonly referred to as upstream–downstream relations. This regional dimension of flood risk calls for catchment‐based approaches in flood risk management as advocated by the EU Flood Directive. In this article, we present and assess the case of an intermunicipal cooperation in Austria which aims to alleviate flood risk and coordinate planning activities based on a catchment approach. The authors apply an established model of water governance to characterise the governance features and to assess the governance qualities and governance capacities of the intermunicipal cooperation. Findings show that the selected case qualifies as a suitable governance instrument to address the main policy objectives. Existing functional ties, shared (flooding) experiences, and mutual trust mark key success factors, indicating that proximity – in its many different forms – is crucial to overcome power asymmetries and spatial misfits in catchment‐based flood risk management. However, intermunicipal cooperation is weak when it comes to ensuring binding land use regulations, showing the need for a complementary use of governance arrangements and formal instruments of regional land use planning in flood risk management.

Beyond ‘just’ flood risk management: the potential for—and limits to—alleviating flood disadvantage - O’Hare, Paul; White, Iain (Regional Environmental Change, 2018)
The threat of flooding poses a considerable challenge for justice. Not only are more citizens becoming exposed to risk, but they are expected to play increasingly active roles in flood risk management. However, until recently, few efforts have charted broader understandings of disadvantage relating to flood risk exposure. Drawing upon social science scholarship that has long been sensitive to concerns related to justice, we deploy and develop the notion of flood disadvantage as a means to assess the challenges to more ‘just’ flood risk management. We contend that the concept of flood disadvantage offers a useful lens to appreciate the constraints of technical approaches to flood risk management, in particular, its limited ability to incorporate complex social elements such as how individuals have differing vulnerabilities and sensitivities to flooding and uneven abilities to engage with risk agendas. The notion highlights the compounding interactions between flooding and other social disadvantages across multiple public policy areas and scales. We argue a fuller acknowledgement of the socio-spatial-temporal dimensions of intersecting disadvantages can help sensitise technical risk analyses that tend to see people and communities as homogeneous entities in a given spatiality. In doing so we can better reveal why some individuals or communities are more vulnerable to disasters or are slower to recover than others. Finally, we outline the challenges in turning more ‘just’ flood risk management from an abstract notion into one that could inform future practice.

Flood Risk Management: Exploring the Impacts of the Community Rating System Program on Poverty and Income Inequality - Noonan, Douglas S.; Sadiq, Abdul‐Akeem A. (Risk Analysis, 2018)
Abstract Flooding remains a major problem for the United States, causing numerous deaths and damaging countless properties. To reduce the impact of flooding on communities, the U.S. government established the Community Rating System (CRS) in 1990 to reduce flood damages by incentivizing communities to engage in flood risk management initiatives that surpass those required by the National Flood Insurance Program. In return, communities enjoy discounted flood insurance premiums. Despite the fact that the CRS raises concerns about the potential for unevenly distributed impacts across different income groups, no study has examined the equity implications of the CRS. This study thus investigates the possibility of unintended consequences of the CRS by answering the question: What is the effect of the CRS on poverty and income inequality? Understanding the impacts of the CRS on poverty and income inequality is useful in fully assessing the unintended consequences of the CRS. The study estimates four fixed‐effects regression models using a panel data set of neighborhood‐level observations from 1970 to 2010. The results indicate that median incomes are lower in CRS communities, but rise in floodplains. Also, the CRS attracts poor residents, but relocates them away from floodplains. Additionally, the CRS attracts top earners, including in floodplains. Finally, the CRS encourages income inequality, but discourages income inequality in floodplains. A better understanding of these unintended consequences of the CRS on poverty and income inequality can help to improve the design and performance of the CRS and, ultimately, increase community resilience to flood disasters.

A comparison of simplified conceptual models for rapid web-based flood inundation mapping - McGrath, Heather; Bourgon, Jean-François; Proulx-Bourque, Jean-Samuel; Nastev, Miroslav; Abo El Ezz, Ahmad (Natural Hazards, 2018)

What determines flood risk perception? A review of factors of flood risk perception and relations between its basic elements - Lechowska, Ewa (Natural Hazards, 2018)
While the methods of risk analysis are generally based on objective measurements, the subjective assessment of risk, such as risk perception, is currently considered a crucial aspect in the context of flood risk management. Risk perception is regarded as an assessment of the perceived probability of hazard and the perceived probability of the results (most often—negative consequences). The work attempts to answer the question: What determines flood risk perception? The knowledge of the factors influencing flood risk perception can solve the issue of the society’s underestimation of flood risk. This issue was considered both in terms of the impact of particular factors on flood risk perception and the interrelationship between three characteristics of flood risk perception: preparedness, worry and awareness. The results were developed based on critical analysis of the empirical research. The review shows that the way particular characteristics determine flood risk perception is not clear and many authors show the diverse conclusions from the similar research. Taking into account various research results, the following factors were distinguished: primary (which clearly influence risk perception), secondary (which influence it unclearly and require further research) and intervening (often describing the context). The organization of the results of the research on the flood risk assessment conducted herein aims to improve the understanding of the human perception of flood risk and, as a result, will lead to the decrease in flood risk by improving the communication of the issue and motivating the residents of the endangered areas to take actions that reduce the negative effects of floods.

Prenatal maternal stress is associated with toddler cognitive functioning: The Iowa Flood Study - Laplante, David P.; Hart, Kimberley J.; O'Hara, Michael W.; Brunet, Alain; King, Suzanne (Early Human Development, 2018)
Keywords: Brunet_Alain

Towards integrated flood management along the lower Rhine and Mississippi Rivers and the international legacy of the 2005 New Orleans Hurricanes Katrina–Rita flood disaster - Hudson, Paul F. (International Journal of River Basin Management, 2018)
Keywords: Ouvrage_Collectif_Numéro1

A real-time hourly water index for flood risk monitoring: Pilot studies in Brisbane, Australia, and Dobong Observatory, South Korea - Deo, Ravinesh C.; Byun, Hi-Ryong; Kim, Ga-Byn; Adamowski, Jan F. (Environmental Monitoring and Assessment, 2018)

Environmental injustice and flood risk: a conceptual model and case comparison of metropolitan Miami and Houston, USA - Collins, Timothy W.; Grineski, Sara E.; Chakraborty, Jayajit (Regional Environmental Change, 2018)

Regionalizing Flood Magnitudes using Landscape Structural Patterns of Catchments - Amiri, Bahman Jabbarian; Junfeng, Gao; Fohrer, Nicola; Mueller, Felix; Adamowski, Jan (Water Resources Management, 2018)

Is Flood Risk Capitalised Into Property Values? - Beltrán, Allan; Maddison, David; Elliott, Robert J. R. (Ecological Economics, 2018)
Keywords: Ouvrage_Collectif_Numéro1

We are our passions: The role of identity processes in harmonious and obsessive passion and links to optimal functioning in society - Bouizegarene, Nabil; Bourdeau, Sarah; Leduc, Caroline; Gousse-Lessard, Anne-Sophie; Houlfort, Nathalie; Vallerand, Robert J. (Self and Identity, 2018)
Keywords: Bourdeau-Brien_Michael; Gousse-Lessard_Anne-Sophie

Investigating added value of regional climate modeling in North American winter storm track simulations - Poan, E. D.; Gachon, P.; Laprise, R.; Aider, R.; Dueymes, G. (Climate Dynamics, 2018)
Extratropical Cyclone (EC) characteristics depend on a combination of large-scale factors and regional processes. However, the latter are considered to be poorly represented in global climate models (GCMs), partly because their resolution is too coarse. This paper describes a framework using possibilities given by regional climate models (RCMs) to gain insight into storm activity during winter over North America (NA). Recent past climate period (1981–2005) is considered to assess EC activity over NA using the NCEP regional reanalysis (NARR) as a reference, along with the European reanalysis ERA-Interim (ERAI) and two CMIP5 GCMs used to drive the Canadian Regional Climate Model—version 5 (CRCM5) and the corresponding regional-scale simulations. While ERAI and GCM simulations show basic agreement with NARR in terms of climatological storm track patterns, detailed bias analyses show that, on the one hand, ERAI presents statistically significant positive biases in terms of EC genesis and therefore occurrence while capturing their intensity fairly well. On the other hand, GCMs present large negative intensity biases in the overall NA domain and particularly over NA eastern coast. In addition, storm occurrence over the northwestern topographic regions is highly overestimated. When the CRCM5 is driven by ERAI, no significant skill deterioration arises and, more importantly, all storm characteristics near areas with marked relief and over regions with large water masses are significantly improved with respect to ERAI. Conversely, in GCM-driven simulations, the added value contributed by CRCM5 is less prominent and systematic, except over western NA areas with high topography and over the Western Atlantic coastlines where the most frequent and intense ECs are located. Despite this significant added-value on seasonal-mean characteristics, a caveat is raised on the RCM ability to handle storm temporal ‘seriality’, as a measure of their temporal variability at a given location. In fact, the driving models induce some significant footprints on the RCM skill to reproduce the intra-seasonal pattern of storm activity.
Keywords: Gachon_Philippe

The impact of flood risk on the price of residential properties: the case of England - Bélanger, Philippe; Bourdeau-Brien, Michael (Housing Studies, 2018)
Keywords: Bourdeau-Brien_Michael; Ouvrage_Collectif_Numéro1

Using tree-rings to determine large wood residence time and transport pulses in a gravel-bed river - Boivin, Maxime; Buffin-Bélanger, Thomas; Arseneault, Dominique (E3S Web of Conferences, 2018)
The Saint-Jean River (SRJ) in Eastern Canada is prone to the formation of very large rafts of wood. Managers of the SJR suspected these jams to influence salmon migration and carried out a dismantling operation to remove large wood accumulated in a 1.2 km long wood raft. This operation became a great opportunity to address key issues relating to large wood dynamics in a fluvial system: residence time and flood contribution to wood recruitment and transport. During the dismantling, we systematically sampled 319 trees from which year of death could be estimated from dendrochronology and year of accumulation in the raft could be obtained from satellite and aerial photos. These two dates allowed us to quantify the residence time for 262 datable large wood (LW) within the fluvial system, to examine the peak years of LW recruitment and to correlate the raft growth rate with hydrometeorological conditions since 1993. The results also emphasized four types of LW flood related to wood dynamics: 1) an erosive flood that produces a large amount of wood in river, 2) a mobilizing flood that carries large quantities of wood, 3) a flood mix that both recruits and transports large quantities of wood, and 4) an ice-breakup flood.
Keywords: Boivin_Maxime

Room for Rivers: Risk Reduction by Enhancing the Flood Conveyance Capacity of The Netherlands’ Large Rivers - Klijn, Frans; Asselman, Nathalie; Wagenaar, Dennis (Geosciences, 2018)
Keywords: Ouvrage_Collectif_Numéro1

Participatory mapping of ecosystem services to understand stakeholders’ perceptions of the future of the Mactaquac Dam, Canada - Reilly, Kate; Adamowski, Jan; John, Kimberly (Ecosystem Services, 2018)

Supply and Transport Limitations on Phosphorus Losses from Agricultural Fields in the Lower Great Lakes Region, Canada - Plach, Janina M.; Macrae, Merrin L.; Ali, Genevieve A.; Brunke, Richard R.; English, Michael C.; Ferguson, Gabrielle; Lam, W. Vito; Lozier, Tatianna M.; McKague, Kevin; O'Halloran, Ivan P.; Opolko, Gilian; Van Esbroeck, Christopher J. (Journal of Environmental Quality, 2018)
Phosphorus (P) mobilization in agricultural landscapes is regulated by both hydrologic (transport) and biogeochemical (supply) processes interacting within soils; however, the dominance of these controls can vary spatially and temporally. In this study, we analyzed a 5‐yr dataset of stormflow events across nine agricultural fields in the lower Great Lakes region of Ontario, Canada, to determine if edge‐of‐field surface runoff and tile drainage losses (total and dissolved reactive P) were limited by transport mechanisms or P supply. Field sites ranged from clay loam, silt loam, to sandy loam textures. Findings indicate that biogeochemical processes (P supply) were more important for tile drain P loading patterns (i.e., variable flow‐weighted mean concentrations ([ C f ]) across a range of flow regimes) relative to surface runoff, which trended toward a more chemostatic or transport‐limited response. At two sites with the same soil texture, higher tile [ C f ] and greater transport limitations were apparent at the site with higher soil available P (STP); however, STP did not significantly correlate with tile [ C f ] or P loading patterns across the nine sites. This may reflect that the fields were all within a narrow STP range and were not elevated in STP concentrations (Olsen‐P, ≤25 mg kg −1 ). For the study sites where STP was maintained at reasonable concentrations, hydrology was less of a driving factor for tile P loadings, and thus management strategies that limit P supply may be an effective way to reduce P losses from fields (e.g., timing of fertilizer application). Core Ideas We used metrics to evaluate controls on edge‐of‐field phosphorus losses. We examined a 5‐yr database of stormflow events (all seasons, including winter). Tile P runoff trended toward being more supply limited than surface runoff.

Responding to Disaster-Related Loss and Grief: Recovering From the 2013 Flood in Southern Alberta, Canada - Fulton, Amy E.; Drolet, Julie (Journal of Loss and Trauma, 2018)
Keywords: Ouvrage_Collectif_Numéro1

Suicidal ideation, plans, and attempts among public safety personnel in Canada. - Carleton, R. Nicholas; Afifi, Tracie O.; Turner, Sarah; Taillieu, Tamara; LeBouthillier, Daniel M.; Duranceau, Sophie; Sareen, Jitender; Ricciardelli, Rosemary; MacPhee, Renée S.; Groll, Dianne; Hozempa, Kadie; Brunet, Alain; et al. (Canadian Psychology / Psychologie canadienne, 2018)
Keywords: Brunet_Alain

Mental Disorder Symptoms among Public Safety Personnel in Canada - Carleton, R. Nicholas; Afifi, Tracie O.; Turner, Sarah; Taillieu, Tamara; Duranceau, Sophie; LeBouthillier, Daniel M.; Sareen, Jitender; Ricciardelli, Rose; MacPhee, Renee S.; Groll, Dianne; Hozempa, Kadie; Brunet, Alain; et al. (The Canadian Journal of Psychiatry, 2018)
Background: Canadian public safety personnel (PSP; e.g., correctional workers, dispatchers, firefighters, paramedics, police officers) are exposed to potentially traumatic events as a function of their work. Such exposures contribute to the risk of developing clinically significant symptoms related to mental disorders. The current study was designed to provide estimates of mental disorder symptom frequencies and severities for Canadian PSP. Methods: An online survey was made available in English or French from September 2016 to January 2017. The survey assessed current symptoms, and participation was solicited from national PSP agencies and advocacy groups. Estimates were derived using well-validated screening measures. Results: There were 5813 participants (32.5% women) who were grouped into 6 categories (i.e., call center operators/dispatchers, correctional workers, firefighters, municipal/provincial police, paramedics, Royal Canadian Mounted Police). Substantial proportions of participants reported current symptoms consistent with 1 (i.e., 15.1%) or more (i.e., 26.7%) mental disorders based on the screening measures. There were significant differences across PSP categories with respect to proportions screening positive based on each measure. Interpretation: The estimated proportion of PSP reporting current symptom clusters consistent with 1 or more mental disorders appears higher than previously published estimates for the general population; however, direct comparisons are impossible because of methodological differences. The available data suggest that Canadian PSP experience substantial and heterogeneous difficulties with mental health and underscore the need for a rigorous epidemiologic study and category-specific solutions.
Keywords: Brunet_Alain

Quantifying peat hydrodynamic properties and their influence on water table depths in peatlands of southern Quebec (Canada) - Bourgault, Marc‐André; Larocque, Marie; Garneau, Michelle; Roux, Marjolaine (Ecohydrology, 2018)
Abstract Water table depth in peatlands is strongly linked to physical properties of the peat, such as density (ρ dry ), peat composition and humification, hydraulic conductivity (K), and specific yield (S y ). Dry bulk density and peat depth are commonly used as indicators of K in ecohydrological models. However, no mathematical relationship exists to quantify S y based on K and ρ dry . As a result, ecohydrological models cannot explicitly reproduce the strong buffering capacity of peatlands. The objectives of this study were to analyse the literature‐reported mathematical link between all the physical properties to develop new mathematical relationships between these parameters and to evaluate whether variations in the physical properties of the peat control water table depth in peatlands. Seven peatlands located in the St. Lawrence Lowlands (Québec, Canada) were sampled, and 1 m long peat cores were collected from up‐gradient, mid‐gradient, and down‐gradient zones. All cores were used to measure ρ dry , K, S y , and to estimate peat composition and humification. Statistically significant correlations were found between (a) K and S y (log–log model), (b) K and depth (log–log model), (c) S y and depth (log–log model), (d) ρ dry and S y (log model), and (e) ρ dry and K (log model). No significant difference was found in either K or S y between sites. However, significant differences were found in water table depths. Because they provide a fuller description of the peat properties that control water table depths, these newly developed functions have the potential to improve the capacity of ecohydrological models to simulate time‐varying hydrological conditions.

The Impact of Flood Zones on Residential Property Prices: The Case of Canada - Bélanger, Philippe; Bourdeau-Brien, Michael; Dumestre, Maxence (Journal of Sustainable Real Estate, 2018)
Keywords: Bourdeau-Brien_Michael; Ouvrage_Collectif_Numéro1

Predicting volume distributions of hardwood sawn products by tree grade in eastern Canada - Bédard, Steve; Duchesne, Isabelle; Guillemette, François; DeBlois, Josianne (Forestry: An International Journal of Forest Research, 2018)
Keywords: Guillemette_Francois

Conceptual Framework for Motivating Actions towards Disaster Preparedness Through Risk Communication - Abunyewah, Matthew; Gajendran, Thayaparan; Maund, Kim (Procedia Engineering, 2018)
Keywords: Ouvrage_Collectif_Numéro1

Urban resilience implementation: A policy challenge and research agenda for the 21st century - Coaffee, Jon; Therrien, Marie‐Christine; Chelleri, Lorenzo; Henstra, Daniel; Aldrich, Daniel P.; Mitchell, Carrie L.; Tsenkova, Sasha; Rigaud, Éric; the participants (Journal of Contingencies and Crisis Management, 2018)
Keywords: Ouvrage_Collectif_Numéro1

The “Lac-Mégantic tragedy” seen through the lens of the EnRiCH Community Resilience Framework for High-Risk Populations - Généreux, Mélissa; Petit, Geneviève; Roy, Mathieu; Maltais, Danielle; O’Sullivan, Tracey (Canadian Journal of Public Health, 2018)
Keywords: Généreux_Mélissa

The Social Life of Heatwave in London: Recasting the Role of Community and Resilience - Nobert, Sebastien; Pelling, Mark (Framing Community Disaster Resilience, 2018)
Keywords: Nobert_Sebastien

Health Risks of Flood Disasters - Paterson, David L; Wright, Hugh; Harris, Patrick N A (Clinical Infectious Diseases, 2018)
Keywords: Ouvrage_Collectif_Numéro1

Risk and Protective Factors for Mental Health and Community Cohesion After the 2013 Calgary Flood - Hetherington, Erin; McDonald, Sheila; Wu, Muci; Tough, Suzanne (Disaster Medicine and Public Health Preparedness, 2018)
Abstract Objective To examine mental health and community cohesion in women living in Calgary after a natural disaster considering previously collected mental health data. Methods Data from an ongoing longitudinal cohort, the All Our Families study, were used to examine mental health and community cohesion 5 months after a major flood in Calgary, Canada. Participants who had completed a baseline questionnaire before the flood were eligible for inclusion in this study (N=923). Four multivariable logistic regression models were built to examine predictors of post-traumatic stress, depression, anxiety, and community cohesion. Results Elevated anxiety before the flood was associated with 2.49 (95% CI: 1.17, 5.26) increased odds of experiencing high levels of post-traumatic stress, regardless of whether respondents lived in a flood-risk community or not. Women who experienced damage to property, or who provided help to others, were more likely to perceive an increased sense of community cohesion (adjusted ods ratio (AOR): 1.67; 95% CI: 1.09, 2.54 and AOR: 1.68; 95% CI: 1.13, 2.52, respectively). Conclusions Women with underlying mental health conditions may be more vulnerable to the psychological impacts of a natural disaster regardless of their level of exposure. Natural disasters may bring communities together, especially those who were more tangibly impacted. ( Disaster Med Public Health Preparedness . 2018;12:470–477)
Keywords: Ouvrage_Collectif_Numéro1

The English National Cohort Study of Flooding and Health: the change in the prevalence of psychological morbidity at year two - Jermacane, Daiga; Waite, Thomas David; Beck, Charles R.; Bone, Angie; Amlôt, Richard; Reacher, Mark; Kovats, Sari; Armstrong, Ben; Leonardi, Giovanni; James Rubin, G.; Oliver, Isabel (BMC Public Health, 2018)
Keywords: Ouvrage_Collectif_Numéro1

The Economic Impact of Hurricane Katrina on Its Victims: Evidence from Individual Tax Returns - Deryugina, Tatyana; Kawano, Laura; Levitt, Steven (American Economic Journal: Applied Economics, 2018)
Hurricane Katrina destroyed over 200,000 homes and led to massive economic and physical dislocation. Using a panel of tax return data, we provide one of the first comprehensive analyses of the hurricane's long-term economic impact on its victims. Hurricane Katrina had large and persistent impacts on where people live, but small and surprisingly transitory effects on employment and income. Within just a few years, Katrina victims' incomes actually surpass that of controls from similar unaffected cities. The strong economic performance of Hurricane Katrina victims is particularly remarkable given that the hurricane struck with essentially no warning. (JEL D14, H24, Q53, R23)
Keywords: Ouvrage_Collectif_Numéro1

Narratives of recovery after floods: Mental health, institutions, and intervention - Butler, Catherine; Walker-Springett, Kate; Adger, W. Neil (Social Science & Medicine, 2018)
Keywords: Ouvrage_Collectif_Numéro1

Research on climate change, health inequities, and migration in the Caribbean - Cloos, Patrick; Ridde, Valéry (The Lancet Planetary Health, 2018)
Keywords: Cloos_Patrick

Using FloodRisk GIS freeware for uncertainty analysis of direct economic flood damages in Italy - Albano, R.; Sole, A.; Adamowski, J.; Perrone, A.; Inam, A. (International Journal of Applied Earth Observation and Geoinformation, 2018)

Mental health and retirement savings: Confounding issues with compounding interest - Bogan, Vicki L.; Fertig, Angela R. (Health Economics, 2018)
Summary The questionable ability of the U.S. pension system to provide for the growing elderly population combined with the rising number of people affected by depression and other mental health issues magnifies the need to understand how these household characteristics affect retirement. Mental health problems have a large and significant negative effect on retirement savings. Specifically, psychological distress is associated with decreasing the probability of holding retirement accounts by as much as 24 percentage points and decreasing retirement savings as a share of financial assets by as much as 67 percentage points. The magnitude of these effects underscores the importance of employer management policy and government regulation of these accounts to help ensure households have adequate retirement savings.
Keywords: Ouvrage_Collectif_Numéro1

A review of the flood risk management governance and resilience literature - Morrison, A.; Westbrook, C.J.; Noble, B.F. (Journal of Flood Risk Management, 2018)
The environmental management literature suggests that resilience is key to managing complex systems and reducing vulnerability resulting from uncertainty and unexpected change. Yet, flood risk management (FRM) has emerged largely from a culture of resistance. This paper takes the pulse of the current state of FRM research, with a focus on how the scholarly community has approached governance for flood resilience. Our analysis of the FRM journal literature identified 258 articles addressing governance and flooding, resilience and adaptation. Five main research themes emerged from these articles, addressing a variety of issues, but mostly lacking the degree of integration needed to address the social‐ecological complexity of FRM. Overall, research supporting the governance of FRM for resilience lacks integration, and methods of mitigating this lack of integration are poorly studied. We conclude with a discussion about the nature and scope of FRM research for resilience, and identify opportunities for more integrative FRM research that is more tightly coupled with policy and practice.
Keywords: Ouvrage_Collectif_Numéro1

Assessing the benefits of serious games to support sustainable decision-making for transboundary watershed governance - Furber, Alison; Medema, Wietske; Adamowski, Jan (Canadian Water Resources Journal / Revue canadienne des ressources hydriques, 2018)

Changes in flood risk governance in France: a David and Goliath story? - Fournier, M.; Larrue, C.; Schellenberger, T. (Journal of Flood Risk Management, 2018)
When analysing flood risk governance in France since the beginning of the 1980s, central government appears as a predominant actor. However, to understand contemporary French flood risk governance ( FRG ), it is also important to highlight how this domination has progressively been undermined since 1982. First, a decentralisation movement has been initiated whose main characteristics are an increasing involvement of local governments and a difficulty for national authorities to maintain their predominant role. The second main change is a diversification in flood risk strategies going together with a diversification in the definition of the flood risk issue. FRG is not a sole matter of protection through defence, preparation, and recovery strategies anymore. Both prevention and mitigation strategies have progressively gained in legitimacy. It is in the latter that local governments and stakeholders have increasingly got involved and have taken up responsibilities and initiatives. The paper focuses on the explanatory factors behind both stability and change, and especially on the ongoing tension, between path dependency factors (i.e. state power and role) and organisational capability of local actors.
Keywords: Ouvrage_Collectif_Numéro1

Serious games as a catalyst for boundary crossing, collaboration and knowledge co-creation in a watershed governance context - Jean, Steven; Medema, Wietske; Adamowski, Jan; Chew, Chengzi; Delaney, Patrick; Wals, Arjen (Journal of Environmental Management, 2018)

Economic inequality and institutional adaptation in response to flood hazards: a historical analysis - Van Bavel, Bas; Curtis, Daniel R.; Soens, Tim (Ecology and Society, 2018)

Qualitative Assessment of Social Vulnerability to Flood Hazards in Romania - Török, Ibolya (Sustainability, 2018)
This paper investigates local-scale social vulnerability to flood hazards in Romania, aiming to identify the most vulnerable social and demographic groups across a wide range of geographical locations by considering three dimensions: demographic, socioeconomic, and the built environment. The purpose of the paper is threefold: first, it strives to improve the Social Vulnerability model (SoVI®) by applying a different weighting method adapted to the Romanian context, taking into consideration the municipalities exposed to flood movements. Second, it aims to develop an assessment model for the most vulnerable communities by measuring the heterogeneity according to local indicators related to disaster risks. Third, it aims to facilitate emergency managers to identify community sub-groups that are more susceptible to loss and to increase the resilience of local communities. To perform local-level vulnerability mapping, 28 variables were selected and three aggregated indexes were constructed with the help of the ArcGIS software. Moreover, a model of Geographically Weighted Regression (GWR) between communities directly affected by floods and localities with high- and very high values of the Local Social Vulnerability Index (LoSoVI) was used to explore the spatial relationship among them and to compare the appropriateness of Ordinary Least Square (OLS) and GWR for such modelling. The established GWR model has revealed that the negative effects of flood hazards are often associated with communities with a high degree of social vulnerability. Thus, the analysis is able to provide a more comprehensive picture on communities in desperate need of financial resources in order to have the ability to diminish the negative impacts of flood hazards and to provide a more sustainable society.

Analyser la vulnérabilité sociétale et territoriale aux inondations en milieu urbain dans le contexte des changements climatiques, en prenant comme cas d'étude la Ville de Montréal - Thomas, I.; Bleau, N. (2018)
28 Figure 7 : limites de la zone inondable et la zone inondée historiquement de la rive de Montréal de la rivière des prairies. [...] 68 Figure 27 : Aperçu de la table d’attributs de la base des données de la description de la sensibilité territoriale. [...] 41 Graphique 3 : Distribution des degrés de la sensibilité sociale par nombre d’aires de diffusion (206 AD au total) du secteur de la rivière des Prairies à Montréal à partir des résultats de l’indice ISSAIP des groupes de l’atelier de travail. [...] Cette analyse implique plusieurs étapes et le développement de plusieurs outils dont : la collecte des données disponibles et nécessaires pour réaliser un état des lieux des zones inondées historiquement pour une partie de la Ville de Montréal, la modélisation de l'espace occupé par l'eau selon différents niveaux d'eau possiblement atteints lors de débordement de la rivière, la collecte des donnée. [...] : la formation de réseaux de communication, la prise de décision, la création de consensus), qu’il est possible de mesurer, mais pas au moyen de données d’archives secondaires.
Keywords: Thomas_Isabelle

Looking for capacities rather than vulnerabilities: The moderating effect of health assets on the associations between adverse social position and health - Roy, Mathieu; Levasseur, Mélanie; Doré, Isabelle; St-Hilaire, France; Michallet, Bernard; Couturier, Yves; Maltais, Danielle; Lindström, Bengt; Généreux, Mélissa (Preventive Medicine, 2018)
Keywords: Généreux_Mélissa